ANDRZEJ BAŃKOWSKI O SŁOWNIKU LINDEGO - LEWASZKIEWICZ, TADEUSZ (Slavia Occidentalis, 2020)
Bańkowski’s review of the first edition of Linde’s Dictionary (1807–1814) and the emendations and supplements introduced by the editors of the second edition of the work (1854–1860) was less than glowing (e.g. “clearly unfinished, prematurely printed”). These opinions need to be firmly rejected. Bańkowski’s nearly 330 statements inserted in the entries of his etymological dictionary contain mostly or at least partially valid observations concerning Linde’s Dictionary. Linde’s lexicographic work did, in fact, represent an important reading source for Mickiewicz. However, Bańkowski’s opinion that it had a decisive influence on the poet’s linguistic development cannot be corroborated.